Criminological Theory and State Crime: How Far Can it Go? (Teoría criminológica y crímenes de Estado: ¿cuán lejos se puede llegar?) - Dawn Rothe (Crítica Penal y Poder, 2013)
Understanding and analyzing state crimes, in all their various forms (e.g., state-corporate crime, crimes of globalization, international crimes, supranational crimes, and political crimes), present challenges for criminologists, jurists, and socio-legal scholars. This is especially the case when trying to apply criminological theory. One should, however, first consider the purpose of theory. For example whether a theory for crimes of the state can or should be parsimonious, falsifiable, or quantifiable are factors that impact the development and acceptance of a theory for crimes of the state. This article discusses these issues and their impact on theoretical development for the field and suggests that any efforts to develop a theory for crimes of the state must recognize the interdependent nature of reality and their complexities. Given this, an overview of criminological theories that have been applied to certain components of state crime is offered followed by an integrated theoretical framework that can be applied to the various forms of state crime.